The gingerbread boy - Egielski, Richard (New York, N.Y. : Laura Geringer Book, 1997)
A freshly baked gingerbread boy escapes when he is taken out of the oven and eludes his pursuers until he meets a clever fox.
6 13 18 19 31
Keywords: Fairy tales; Folklore